The Effect of Customer Experience and Responsiveness on Customer Lifetime Value (CLV) of Online Service Users - Purba, Alan Smith; Ulfah, Yana (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
This study aims to analyze the effect of customer experience and responsiveness on customer lifetime value (CLV) among online service users. An associative quantitative approach was employed using a survey method involving 303 students of the undergraduate accounting program at Mulawarman University who are active users of digital platforms such as e-commerce and online transportation. Data were collected via questionnaires and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that both customer experience and responsiveness have a positive and significant effect on CLV, both partially and simultaneously. The coefficient of determination (R²) of 0.564 indicates that 56.4% of the variation in CLV is explained by the two independent variables. The regression model satisfies classical assumptions, with no detected issues of autocorrelation, heteroscedasticity, and data approaching a normal distribution. These findings highlight the importance of enhancing customer experience and service responsiveness in building long-term customer value in the digital era